(untitled) (Urdimento - Revista de Estudos em Artes Cênicas, 2018)
This text was presented at the round table: "Dialogues between tradition and innovation in current pedagogy", which composed the program of the 2nd International meeting on training in the arts of puppetry, which took place in Romania on June 2017. In it, more than answers are raised inquiries from a central question: to what extent and how has the artistic heritage transmission forms been operated today with a central focus on puppet theater? Taking as a guide the discussions held at the Seminar "Arts of Transmission and Artistic Heritage", a joint initiative of University of Évora and the Marionette Museum of Lisbon (Museu da Marioneta de Lisboa), and focusing on two forms of puppetry traditions - Bonecos de Santo Aleixo - BSA, from Alentejo, Portugal, and the Mamulengo, from Pernambuco, Brazil, this article seeks to discuss some tensions operated in transmissions processes.